InSAR Observations of Construction‐Induced Coastal Subsidence on Miami's Barrier Islands, Florida - Farzaneh Aziz Zanjani; Falk Amelung; Andreas Piter; Khaled Sobhan; Amin Tavakkoliestahbanati; Gregor P. Eberli; Mahmud Haghshenas Haghighi; Mahdi Motagh; Pietro Milillo; Sara Mirzaee; Antonio Nanni; Esber Andiroglu (Earth and Space Science)
Abstract This study utilizes Interferometric Synthetic Aperture Radar (InSAR) to examine subsidence along the coastal strip of the Miami barrier islands from 2016 to 2023. Using Sentinel‐1 data, we document vertical displacements ranging from 2 to 8 cm, affecting a total of 35 coastal buildings and their vicinity. About half of the subsiding structures are younger than 2014 and at the majority of them subsidence decays with time. This correlation suggests that the subsidence is related to construction activities. In northern and central Sunny Isles Beach, where 23% of coastal structures were built during the last decade, nearly 70% are experiencing subsidence. The majority of the older subsiding structures show sudden onset or sudden acceleration of subsidence, suggesting that this is due to construction activities in their vicinity; we have identified subsidence at distance of 200 m, possibly up to 320 m, from construction sites. We attribute the observed subsidence to load‐induced, prolonged creep deformation of the sandy layers within the limestone, which is accelerated, if not instigated, by construction activities. Distant subsidence from a construction site could indicate extended sandy deposits. Anthropogenic and natural groundwater movements could also be driving the creep deformation. This study demonstrates that high‐rise construction on karstic barrier islands can induce creep deformation in sandy layer within the limestone succession persisting for a decade or longer. It showcases the potential of InSAR technology for monitoring both building settlement and structural stability.